From media systems to media cultures : understanding socialist television - Mihelj, Sabina; Huxtable, Simon, 1980- (Cambridge, United Kingdom ; New York : Cambridge University Press, 2018)
"In From Media Systems to Media Cultures: Understanding Socialist Television, Sabina Mihelj and Simon Huxtable delve into the fascinating world of television under communism, using it to test a new framework for comparative media analysis. To understand the societal consequences of mass communication, the authors argue that we need to move beyond the analysis of media systems, and instead focus on the role of the media in shaping cultural ideals and narratives, everyday practices and routines. Drawing on a wealth of original data derived from archival sources, programme and schedule analysis, and oral history interviews, the authors show how communist authorities managed to harness the power of television to shape new habits and rituals, yet failed to inspire a deeper belief in communist ideals. This book and their analysis contains important implications for the understanding of mass communication in non-democratic settings, and provides tools for the analysis of media cultures globally"--
Includes bibliographical references (pages 330-358)
Keywords: Communism and mass media; Mass media -- Political aspects; Mass media -- Economic aspects; Mass media and culture; POLITICAL SCIENCE / Government / International